Effects of Brand Name Exposure on Brand Choice: An Implicit Memory Perspective - CHUNG, Seh-Woong (Institutional Knowledge at Singapore Management University, 1997)
Drawing on the implicit memory framework, this study examines how exposures to brand names affect subsequent brand choices under different involvement conditions. Experimental results show that exposure modality (i.e., visual vs. auditory) affects brand choices more under low involvement than under high involvement. Subjects are more likely to choose the brand when the prior exposure to the brand is visual than when it is auditory. However, the study finds that processing mode (conceptual vs. perceptual) has no effect on brand choice. Theoretical and practical implications are discussed along with suggestions for future research.